Dekadensi Moral di Kalangan Pelajar (Revitalisasi Strategi PAI dalam Menumbuhkan Moralitas Generasi Bangsa) - Mochamad Iskarim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Globalization is shown by the development in science and technology which brings great effects including the positive and negative one. One of the negative effects of globalization is the emergence of consumerism, hedonism, and secularism which causes moral decadence of the nations. The worse condition of this condition can be seen from the bad attitude and behavior of the students. Therefore, Islamic education which has main role in constructing moral of the students should be rearranged to solve this problem. This condition shows the importance of revitalizing the strategy of Islamic education in minimizing moral decadence of the nations.